KARAKTERISTIK DIMENSI UTAMA KAPAL JARING RAMPUS DI PELABUHAN PERIKANAN NUSANTARA KARANGANTU KOTA SERANG PROVINSI BANTEN - Iyoh Istiqomah; Adi Susanto; Ririn Irnawati (Jurnal Perikanan dan Kelautan, 2014)
Bottom gillnet was classified into static fishing gear that require high stability. The main dimensions of the ship are very important in the manufacture of fishing boats. The main dimensions of the ship ratio (L/B, L/D and B/D) greatly affects to the stability, strength and speed. The lack of availability of information and data collection on the main dimensions can be an obstacle in the development of fishing activities. The experiment was conducted in April-October 2014 in Karangantu Archipelagic fshing port Serang city Banten Province. The results showed the main dimensions of the ships have range of LOA= 6.76-13.43 m, Bmax= 1.50-3.00 m and D= 0.27-1.04 m. The main dimension of ratio the ships have range of L/B is 2.60-6.67; L/D is 8.65-28.15 and B/D is 1.50-8.15. The engine powers that are widely used is 16 and 24 PK. The fishermen did not use the main dimensions ratio to determine the length of bottom gillnet and engine power.Keyword: bottom gillne, main dimensions, ratio, ship